iNOS Activity Is Required for the Therapeutic Effect of Mesenchymal Stem Cells in Experimental Systemic Sclerosis - Maria, Alexandre T. J.; Rozier, Pauline; Fonteneau, Guillaume; Sutra, Thibault; Maumus, Marie; Toupet, Karine; Cristol, Jean-Paul; Jorgensen, Christian; Guilpain, Philippe; Noël, Danièle (Frontiers in Immunology, 2018)
Objectives: Fibrosis is a hallmark of systemic sclerosis (SSc), an intractable disease where innovative strategies are still being sought. Among novel anti-fibrotic approaches, mesenchymal stromal/stem cell (MSC)-based therapy appears promising. Previously, we reported anti-fibrotic effects of MSC in an experimental model of SSc, through various mechanisms (tissue remodeling, immunomodulation, anti-oxidant defense). Since immunomodulation is a pivotal mechanism for MSC therapeutic effects, we investigated the specific role of critical molecules associated with MSC immunosuppressive properties and hypothesized that MSC defective for these molecules would be less effective in reducing fibrosis in SSc. Methods: SSc was induced by 6-week daily intradermal injections of hypochlorite (HOCl) in mice. MSC were isolated from the bone marrow of wild type mice (WT) or mice knockout for IL1RA, IL6, or iNOS (IL1RA−/−, IL6−/−, or iNOS−/− MSC, respectively). Treated-mice received 2.5 × 105 MSC intravenous infusion at d21. Skin thickness, histological and biological parameters were evaluated in skin and blood at d42. Results: IL1RA−/− and IL6−/− MSC exerted similar anti-fibrotic properties as WT MSC, with a reduction of skin thickness together with less collagen deposition. Conversely, iNOS−/− MSC did not exert anti-fibrotic functions as shown by a similar skin thickness progression as non-treated HOCl-SSc mice. Compared with WT MSC, iNOS−/− MSC kept some immunosuppressive and tissue remodeling properties, but lost their capacity to reduce oxidative stress in HOCl-SSc mice. Conclusion: Our study highlights the crucial role of iNOS, whose activity is required for the anti-fibrotic properties of MSC in experimental SSc, with a special emphasis on NO-related anti-oxidant functions.